FORMULATION AND EVALUATION OF FLOATING BEADS OF DILTIAZEM HCL - AGARWAL, SHIVENDRA; ZAMIL, FARAZ; SINGH, LOKENDRA; SAXENA, AMIT (International Journal of Current Pharmaceutical Research, 2016)
Objective: Diltiazem, a benzothiazepine calcium channel blocker, is used alone or with an angiotensin-converting enzyme inhibitor, to treat hypertension, chronic stable angina pectoris, and Prinzmetal's variant angina. The elimination half-life of Diltiazem is 3 to 4.5 h. In the present research work multiple units floating drug delivery systems of Diltiazem Hydrochloride were prepared by using sodium alginate, mustard oil and olive oil. Methods: The floating systems were prepared by using emulsion gelation technique to improve gastric retention. The prepared beads were evaluated for physical characterization floating lag time, total floating time, swelling index and in vitro drug release studies. The prepared beads were found to be spherical, free flowing and remain buoyant for 24 h with a short floating lag time. Results: Percentage drug content of beads in the formulation F9 For olive oil and H8 for mustard oil was found to be in the range of 95.89 to 54.08%. Swelling properties of all formulation increased as the concentration of SCMC increased. The particle size increased as the amount of polymer was increased in each formulation. Conclusion: Floating beads of Diltiazem HCL could prompt a potential sustained drug delivery over an extend period of time that can reduce dose frequency. It was also found that the cumulative drug release from all formulations was found to be between 94.93 to 100.042.